2019
DOI: 10.3390/cryst9030163
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Controlled Photocatalysis and Chemical Sensing of TiO2, α-Fe2O3, and Cu2O Nanocrystals

Abstract: A relatively new approach to the design of photocatalytic and gas sensing materials is to use the shape-controlled nanocrystals with well-defined facets exposed to light or gas molecules. An abrupt increase in a number of papers on the synthesis and characterization of metal oxide semiconductors such as a TiO2, α-Fe2O3, Cu2O of low-dimensionality, applied to surface-controlled photocatalysis and gas sensing, has been recently observed. The aim of this paper is to review the work performed in this field of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 223 publications
0
9
0
Order By: Relevance
“…Charge recombination occurring at crystal defects is indicated by the peaks occurring at 460 nm while charge recombination due to ∼dangling bonds is indicated by PL spectra not going back to 0 CPS at the longer wavelengths. 46 Therefore, the PL spectra for the nanohybrids indicates that they have O vacancies but do not have any dangling bonds ( Fig. 8(b)–(d) ).…”
Section: Resultsmentioning
confidence: 91%
“…Charge recombination occurring at crystal defects is indicated by the peaks occurring at 460 nm while charge recombination due to ∼dangling bonds is indicated by PL spectra not going back to 0 CPS at the longer wavelengths. 46 Therefore, the PL spectra for the nanohybrids indicates that they have O vacancies but do not have any dangling bonds ( Fig. 8(b)–(d) ).…”
Section: Resultsmentioning
confidence: 91%
“…A powerful way to boost the photocatalytic activity of inorganic semiconductor crystals for dye degradation, water splitting, CO 2 reduction, and organic transformation reactions is to use catalysts exposing appropriate surfaces, as some crystal faces are much more active than others. [1][2][3][4][5] For semiconductors with a cubic unit cell, Cu 2 O, Ag 2 O, Ag 3 PO 4 , and SrTiO 3 crystals have displayed strong facet dependence in photocatalytic activity. [6][7][8][9] For example, Cu 2 O rhombic dodecahedra have a high photocatalytic activity, but cubes are simply inert.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous reports on dynamic working temperature modulation focused primarily on the investigation of heating-voltage waveform manipulation and algorithm improvement, not involving the insight of the temperature modulation sensing behaviors. , Furthermore, few reports utilized nanostructured metal oxide, let alone their finer nanostructures . Actually, besides different compositions of nanostructured metal oxide crystals, their different facets also exhibit different gas sensing performances, which lie in different reactivities arising from different atomic arrangements. , For example, Han et al demonstrated that the relative response of SnO 2 to ethanol was enhanced by increasing exposure to {221} facets . Jiang et al demonstrated that the {111} facet of SnO 2 was most active toward benzene combustion .…”
Section: Introductionmentioning
confidence: 99%
“…26 Actually, besides different compositions of nanostructured metal oxide crystals, their different facets also exhibit different gas sensing performances, which lie in different reactivities arising from different atomic arrangements. 27,28 For example, Han et al demonstrated that the relative response of SnO 2 to ethanol was enhanced by increasing exposure to {221} facets. 29 that the {111} facet of SnO 2 was most active toward benzene combustion.…”
Section: ■ Introductionmentioning
confidence: 99%